Integrative immunogenomic analysis of gastric cancer dictates novel immunological classification and the functional status of tumor‐infiltrating cells. Issue 10 (17th October 2020) - Sato, Yasuyoshi; Wada, Ikuo; Odaira, Kosuke; Hosoi, Akihiro; Kobayashi, Yukari; Nagaoka, Koji; Karasaki, Takahiro; Matsushita, Hirokazu; Yagi, Koichi; Yamashita, Hiroharu; Fujita, Masashi; Watanabe, Shuichi; et al.
Abstract: Objectives: A better understanding of antitumor immunity will help predict the prognosis of gastric cancer patients and tailor the appropriate therapies in each patient. Therefore, we propose a novel immunological classification of gastric cancer. Methods: We performed whole‐exome sequencing (WES), RNA‐Seq and flow cytometry in 29 gastric cancer patients who received surgery. The TCGA data set of 323 gastric cancer patients and RNA‐Seq data of 45 patients who received pembrolizumab (Kim et al . Nat Med 2018; 24 : 1449–1458) were also analysed. Results: Immunogram analysis of cancer–immunity interaction of gastric cancer revealed immune signatures of four main types, designated Hot1, Hot2, Intermediate and Cold. Immunologically hot tumors displayed a dysfunctional T‐cell signature, while cold tumors had an exclusion signature. Ex vivo tumor‐infiltrating lymphocyte analysis documented T‐cell dysfunction with the expression of checkpoint molecules and impaired cytokine production. The T‐cell function was more profoundly damaged in Hot1 than Hot2 tumors. Patients in Hot2 subtypes had better survival in our cohort and TCGA cohort. Although these immunological subtypes overlapped to some degree with the molecular subtypes in the TCGA, intratumoral immune responses cannot be predicted solely based on histological or molecular subtyping of gastric cancer. Molecular and immunological classifications complement each other to predict the responses to anti‐PD‐1 therapy and have the potential to be a biomarker for the treatment of gastric cancer. Conclusion: The immunological classification of gastric cancer resulted in four subtypes. Hot tumors were further divided into two subtypes, between which the functional status of T cells was different. Abstract : In this study, an integrative immunogenomic analysis of gastric cancer was performed. The immunological classification of gastric cancer resulted in immune signatures of four main types, designated Hot1, Hot2, Intermediate and Cold, in which the functional status of T cells was different. Early administration of anti‐PD‐1 therapy might be recommended for patients with Hot1 tumors.